2017
DOI: 10.2337/dc16-1974
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes in the Real World: The Elusive Nature of Glycemic Control

Abstract: Despite U.S. Food and Drug Administration (FDA) approval of over 40 new treatment options for type 2 diabetes since 2005, the latest data from the National Health and Nutrition Examination Survey show that the proportion of patients achieving glycated hemoglobin (HbA 1c ) <7.0% (<53 mmol/mol) remains around 50%, with a negligible decline between the periods 2003-2006 and 2011-2014. The Healthcare Effectiveness Data and Information Set reports even more alarming rates, with only about 40% and 30% of patients ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
196
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(206 citation statements)
references
References 41 publications
4
196
0
6
Order By: Relevance
“…Our results are in line with those of a recent metaanalysis of 43 RCTs (overall 16 590 participants) assessing the effects of the addition of a third drug after failure of dual therapy. 23,24 Our results also suggest that the best glycaemic control is achieved in the elderly and in patients with comorbid conditions, whereas the worst control was observed among women. A great number of treatment options show notable efficacy in RCTs, but their impact on glycaemic control in real-world clinical practice is usually less than expected.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our results are in line with those of a recent metaanalysis of 43 RCTs (overall 16 590 participants) assessing the effects of the addition of a third drug after failure of dual therapy. 23,24 Our results also suggest that the best glycaemic control is achieved in the elderly and in patients with comorbid conditions, whereas the worst control was observed among women. A great number of treatment options show notable efficacy in RCTs, but their impact on glycaemic control in real-world clinical practice is usually less than expected.…”
Section: Discussionsupporting
confidence: 57%
“…21,22 Conversely, the achievement of the other two goals (HbA1c <7% or < 8%) was inferior with insulin and GLP-1RAs, probably because of the higher preintensification HbA1c levels in these two groups (9.4% for insulin and 9.1% for GLP-1RAs vs. 8.7-9.0%). 23 It has been suggested that poor adherence is the key factor explaining the gap between results from real-world studies and RCTs. 6 The authors concluded that rapid-acting insulin added to metformin and SUs resulted in the largest reduction in HbA1c after 24-36 weeks (1.6% vs. placebo), followed by GLP-1RA (1.0%), basal insulin (0.8%), and SGLT-2i and DPP4i (both 0.7%).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent cohort study using a large EHR-administrative claims database, poor medication adherence was the primary factor explaining smaller HbA1c reductions among patients receiving usual care in the real-word compared to participants in RCTs [49]. In order to realize HbA1c improvements achieved in RCTs, approaches for improving adherence must be easily implemented in real-world clinical practice and account for multiple adherence barriers [50]. In future research, we plan to improve the efficiency of our barriers assessment, both by reducing the number of items and exploring alternative methods of administration (e.g., via tablet, phone, or kiosks in clinic waiting rooms).…”
Section: Discussionmentioning
confidence: 99%
“…Cifras recientes indican que su prevalencia en adultos de veinte o más años de edad, pasó de 9.2% en el año 2012 a 9.4% en el año 2016 (ENSANUT MC, 2016). Sin embargo, uno de los principales problemas vinculados a la aparición de complicaciones asociadas a la DM2 y a un peor estado de salud es precisamente la falta de adherencia al tratamiento (Edelman & Polonsky, 2017;Jiménez-Corona & Aguilar-Salinas, 2013;Shams, Amjad, Kumar, Ahmed, & Saleem, 2016).…”
Section: Introductionunclassified